The Boy Allies in Great Peril; Or, With the Italian Army in the Alps - Hayes, Clair W. (Clair Wallace), 1887- (Salt Lake City, UT : Project Gutenberg, 2004)
"The Boy Allies in Great Peril; Or, With the Italian Army in the Alps" by Clair W. Hayes is a historical adventure novel written in the early 20th century. The story follows two American boys, Hal Paine and Chester Crawford, who have previously fought alongside various Allied forces during World War I and now find themselves amid the tensions in Italy as the country leans towards entering the war against Austria. The opening chapters establish a thrilling narrative filled with action and intrigue, as the boys become embroiled in a plot involving espionage, theft, and the imminent declaration of war. At the start of the novel, Hal and Chester are caught up in a chaotic crowd outside a palace in Rome, anxiously anticipating news of Italy's potential war declaration. Their fateful encounter with an Italian army officer leads to a struggle with a man who steals a vital document. In a series of events marked by quick-thinking and bravery, Hal and Chester aim to recover the stolen paper, but they soon find themselves facing threats from both enemy spies and suspicions from the Italian military. As the boys navigate danger and deception, their resolve is tested, highlighting their courage and camaraderie in the face of perilous challenges. The opening portion sets the stage for an exciting adventure that promises to blend personal heroism with the larger conflicts of the war. (This is an automatically generated summary.)
Release date is 2004-06-01
E-text prepared by Suzanne Shell, Project Gutenberg Beginners Projects, Mary Meehan, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: World War, 1914-1918 -- Campaigns -- Italy -- Juvenile fiction